Computational creativity issues in generative design and digital fabrication of complex 3D meshes - Roncoroni, Umberto Luigi (2024)
This article describes generative algorithms and Digital Fabrication techniques with organic materials to create complex 3D objects for industrial design, sculpture, and architecture. Experimental artistic production using these algorithms concluded with a solution based on programmable meshes, which use identifiers to control the topological characteristics of vertices during the modeling process. On the other hand, the hybridization of analog and digital techniques was explored through fabrication. Comparing artistic production and hybrid techniques with generative AI, we will discuss topics of Computational Creativity in art, industrial design, and architecture. The programmable meshes solution, combined with hybrid fabrication processes, enables an incredible variety of complex forms, stimulates artistic creativity, and provides flexible feedback to bypass some Digital Fabrication issues. Our findings also elucidate the importance of original technology development and cultural identity in fostering creative and culturally inclusive technologies for art and education.